في سند الحديث النبوي عند بعض المستشرقين (Common Link) شبهة وضع الحديث عن طريق الراوي المركزي: (دراسة تحليلية نقدية) - Anwar, Saepul; Kusnadi (Indra Institute Research & Publication, 2024)
This research delves into studying the suspicion of Hadith fabrication through the concept of the